Optimalisasi Lahan Di Bawah Tegakkan Tanaman Kopi Melalui Budidaya Tanaman Kapulaga (Elletria cardamomum), Di Desa Sumber Rejo, Purwosari, Kabupatrn Pasuruan - Purwadi; Dinna Hadi Sholikah; Jojok Dwiridotjahjon; Purnomo Edi Sasongko (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Sumber Rejo village is one of the villages in Purwosari district, Pasuruan Regency, which is famous for a coffee production. The livelihood of the people of Sumber Rejo village largely relies on the results of coffee plantations and farm workers, where coffee production is still relatively low. The farming results from the 24.3 ha of people's coffee plantation land owned by members of the “Sinar Agro Permata” farmer group, where in the 2024 harvest season, the average is only 2 quintals per hectare of ground dry coffee. In general, the existing conditions of Kucur Hamlet, Sumber Rejo Village, Purwosari District, Pasuruan Regency are as follows: (1) not optimal land use under the coffee plant stand with cardamom biopharmaceutical plant commodities, which are economically very promising. (2) Not many farmers know the high economic value of cardamom plants. (3) The participation of the farmer group “Sinar Agro Permata” in supporting the development and improvement of economic capacity through the development of a cardamom plant commodity nursery. Based on the existing conditions mentioned above, the purpose of community service activities is to help find solutions to problems including 4 (four ) aspects, namely the following : (1) optimization of land under the coffee stand with cardamom plant cultivation, (2) assistance in producing cardamom seeds, (3) assistance in cardamom cultivation on agroforestry land under the coffee plant stand, (4) empowering Poktan” Sinar Agro Permata” in an effort to increase the economic capacity of the community through cardamom breeding efforts. Methods used (1) provide understanding, socialization, and utilization/optimization of land.under the coffee stand with plants of high economic value “cardamom", (2) provide assistance in producing cardamom seeds under the coffee stand, (3) provide assistance in cardamom cultivation techniques on land under the coffee plant stand. (4) Empowering Poktan “Sinar Agro Permata”. The result of community service is cardamom seeds, and a demo of cardamom cultivation plots under the coffee plant stand Keywords: Cardamom, Optimization, Nursery